2017
DOI: 10.1038/s41598-017-06041-1
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Arrangements of Olfactory Receptor Gene Expression in Zebrafish are Established by Radial Movement of Specified Olfactory Sensory Neurons

Abstract: Spatial restriction of olfactory receptor (OR) gene expression in peripheral sense organs is a common phenomenon across species, suggesting that zonal OR expression somehow contributes to olfactory function. In zebrafish OR expression patterns reminiscent of zones occur as concentric domains with preferred diameters for different ORs. However, the function and the developmental origin of the pattern are unknown. Here we investigate olfactory sensory neuron (OSN) neurogenesis in the adult zebrafish olfactory ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(71 citation statements)
references
References 48 publications
(67 reference statements)
8
62
0
1
Order By: Relevance
“…Lastly, any potential mechanism has to take into account the constant renewal of olfactory sensory neurons during adult life. The average lifetime of zebrafish OSN has been estimated as around one month [ 29 ], so at the age examined, several rounds of neurogenesis have already occurred blurring any potential relation to organismal age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, any potential mechanism has to take into account the constant renewal of olfactory sensory neurons during adult life. The average lifetime of zebrafish OSN has been estimated as around one month [ 29 ], so at the age examined, several rounds of neurogenesis have already occurred blurring any potential relation to organismal age.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the zebrafish olfactory organ possesses two proliferative zones, one at the apex of the lamella, the other at the outer border of the sensory region [ 30 ] . A recent publication [ 29 ] examining three zebrafish odorant receptor genes has suggested that different olfactory progenitor cells might migrate differentially from these proliferative zones, which could result in a pattern of broad expression zones with different centers-of-gravity . While beyond the scope of the current investigation, it will be interesting to see whether OlfC genes follow a similar pattern.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to having a well-characterized morphology and neuronal circuitry, the olfactory system of zebrafish presents remarkable regeneration, repair, and reorganization mechanisms in basal states in response to injury. Both the olfactory organ and the olfactory bulb present continuous neurogenesis and neuronal turnover throughout the organism’s lifespan [24,38,39,40,41,42]. These features make the olfactory system of zebrafish an ideal model to study mechanisms of olfaction processing, olfactory dysfunction, and regeneration following damage.…”
Section: The Olfactory System Of Zebrafish: Anatomical Morphologimentioning
confidence: 99%
“…OSNs express a combination of discrete olfactory receptors (ORs), and groups of OSNs expressing the same olfactory receptors are positioned in defined zones within the rosette [38,51,52]. Evidence suggests that zebrafish OSNs follow the “one neuron–one receptor” configuration that has been described in mammals, although a couple of exceptions in ciliated OSNs have been reported [44,53,54].…”
Section: The Olfactory System Of Zebrafish: Anatomical Morphologimentioning
confidence: 99%
See 1 more Smart Citation